Plant breeding evaluation of the red currant cultivar ‘Podarok Pobeditelyam’ and its inbred progeny - O. D. Golyaeva; O. V. Panfilova; O. V. Kalinina (Труды по прикладной ботанике, генетике и селекции)
Background. Inbreeding, as a way to produce progenies from organisms in different degrees of kinship, is an important genetic and breeding technique used to improve various crops, including fruit and berry plants. Inbreeding has not been extensively used with red currant, so a study of the possibility to employ closely related crosses in breeding practice with this crop remains relevant. The purpose of this study was to assess the breeding potential of the red currant cultivar ‘Podarok Pobeditelyam’ by disclosing economic and biological characteristics in its inbred progeny.Methods and materials. The research was carried out at the red currant breeding site of the Russian Research Institute of Fruit Crop Breeding (VNIISPK, Orel) in 2016–2018. The seedlings obtained from the self-pollination of a new red currant cultivar, ‘Podarok Pobeditelyam’, were the objects of the study. Records and observations were carried out according to the program and methodology for breeding and variety studies of fruit, berry and nut crops.Results and conclusion. The percentage of long-cluster seedlings (cluster length > 10 cm) in the inbred progeny of cv. ‘Podarok Pobeditelyam’ was 21.8%; segregation of large-fruited seedlings (berry weight > 0.65 g) was observed at the level of 17%; the maximum degree of transgression (Tsmax) was 42%; and the incidence of transgressive seedlings was 37%. The analysis of the progeny showed that cv. ‘Podarok Pobeditelyam’ is a homozygote for the dominant Rc gene that controls the red color of the berries, and displays donor properties for the trait “dry detachment of berries”. The study of the cultivar’s self-pollinated progeny did not reveal any inbreeding depression in F1 seedlings from closely related crosses as far as plant condition or productivity is concerned. The selected seedlings are of interest for further variety research and use in breeding practice as new source material.